The Nasal Cavity Is a Route for Prion Infection in Hamsters - Kincaid, Anthony E. (American Society for Microbiology, 2007)
Animals that naturally acquire the prion diseases have a well-developed olfactory sense that they utilize for a variety of basic behaviors. To assess the potential for the nasal cavity to serve as a point of entry for prion diseases, a small amount of prion-infected brain homogenate was placed inferior to the nostrils of hamsters, where it was immediately sniffed into the nasal cavity. Hamsters extranasally inoculated with the HY strain of transmissible mink encephalopathy (TME) agent had an incubation period that was not significantly different from per os inoculation of the same dose of the HY TME agent. However, the efficiency of the nasal route of inoculation was determined to be 10 to 100 times greater based on endpoint dilution analysis. Immunohistochemistry on tissues from hamsters killed at 2-week intervals after inoculation was used to identify the disease-associated form of the prion protein (PrP(d)) to determine the route of prion neuroinvasion. Nasal mucosa-associated lymphoid tissue and submandibular lymph nodes initially accumulated PrP(d) as early as 4 weeks postinfection. PrP(d) was first identified in cervical lymph nodes at 8 weeks, in the mesenteric lymph nodes, spleen, and Peyer's patches at 14 weeks, and in the tongue 20 weeks after inoculation. Surprisingly, there was no evidence of PrP(d) in olfactory epithelium or olfactory nerve fascicles at any time after inoculation. Therefore, the HY TME agent did not enter the central nervous system via the olfactory nerve; instead, PrP(d) accumulated in elements of the cranial lymphoreticular system prior to neuroinvasion.